One Special Question to Start with: Can HIF/NFkB be a Target in Inflammation? - A. Russo, Matteo; Sansone, Luigi; Carnevale, Ilaria; Limana, Federica; Runci, Alessandra; Polletta, Lucia; A. Perrone, Giulietta; De Santis, Elena; Tafani, Marco (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2015)
Hypoxia and Inflammation are strictly interconnected with important consequences at clinical and therapeutic level. While cell and tissue damage due to acute hypoxia mostly leads to cell necrosis, in chronic hypoxia, cells that are located closer to vessels are able to survive adapting their phenotype through the expression of a number of genes, including proinflammatory receptors for alarmins. These receptors are activated by alarmins released by necrotic cells and generate signals for master transcription factors such as NFkB, AP1, etc. which control hundreds of genes for innate immunity and damage repair. Clinical consequences of chronic inflammatory reparative response activation include cell and tissue remodeling, damage in the primary site and, the systemic involvement of distant organs and tissues. Thus every time a tissue environment becomes stably hypoxic, inflammation can be activated followed by chronic damage and cell death or repair with vessel proliferation and fibrosis. This pathway can occur in cancer, myocardial infarction and stroke, diabetes, obesity, neurodegenerative diseases, chronic and autoimmune diseases and age-related diseases. Interestingly, proinflammatory gene expression can be observed earlier in hypoxic tissue cells and, in addition, in activated resident or recruited leukocytes. Herewith, the reciprocal relationships between hypoxia and inflammation will be shortly reviewed to underline the possible therapeutic targets to control hypoxia-related inflammation in a number of epidemiologically important human diseases and conditions.
Keywords: inflammation